Determination of oligomeric proanthocyanidins and their antioxidant capacity from different chocolate manufacturing stages using the NP-HPLC-online-DPPH methodology. (1st January 2017) - Pedan, Vasilisa; Fischer, Norbert; Bernath, Konrad; Hühn, Tilo; Rohn, Sascha
Highlights: Cocoa proanthocyanidins were tracked during the chocolate manufacturing process. The antioxidant capacity was assessed simultaneously using the NP-HPLC-online-DPPH. The highest impact on the polyphenol profile occurs during fermentation. The highest impact on polyphenol degradation occurs during roasting process. Higher oligomeric proanthocyanidins possess a high antioxidant activity. Abstract: Cocoa beans are a well-known source of antioxidant polyphenols. Especially individual oligomeric proanthocyanidins demonstrated a significant contribution to the total antioxidant activity of cocoa compared to monomeric compounds. An NP-HPLC-online-DPPH assay was developed for separating the homologous series of oligomeric proanthocyanidins and the simultaneous assessment of their antioxidant capacity in relation to the degree of polymerization (DP). The present study describes the influence of the different stages of a lab-scale chocolate manufacturing process on the content of oligomeric proanthocyanidins and their antioxidant capacity. The sum of the total proanthocyanidin content (∑ DP1-DP13) decreased from 30 mg epicatechin equivalents per gram non-fat dry matter in raw fresh cocoa beans to 6 mg epicatechin equivalents per gram in the final chocolate. The antioxidant capacity decreased accordingly from 25 mg epicatechin equivalents per gram non-fat dry matter in raw fresh cocoa beans to 4 mg/g in the final chocolate product.